Characterization and cryopreservation of semen of four South African chicken breeds - Mosenene, Thatohatsi Madaniel Bernice (University of the Free State, 2009)
The aim of the study was to characterize and evaluate the quality of fresh semen of 4 breeds of chicken and the susceptibility of cockerel semen to a cryopreservation protocol, assessed microscopically for sperm motility and morphology and ultimately fertilizing ability following AI. The differences between breeds were determined by comparing the fertilizing ability and hatchability of fresh and frozen-thawed semen. The study was carried out at Glen Agricultural Development Institute and at the University of the Free State. Four chicken breeds, namely the Rhode Island Red, Potchefstroom Koekoek, New Hampshire and White Leghorn, were used. Qualitative characterization of the semen was performed in 28 cockerels (7 per breed). Semen was collected using the massage technique twice a week in the first trial. The eosin-nigrosin staining technique was used to microscopically evaluate the morphology of the sperm from the different breeds. The fresh semen parameters evaluated were ejaculate volume, semen colour, semen pH, sperm concentration, the percentage live and dead sperm, sperm motility and the abnormalities of the sperm. The percentage live and dead sperm, sperm motility and abnormalities were also evaluated for the frozen-thawed cockerel semen. During the second phase of the study, semen was collected 3 times per week from the same cockerels. Semen was frozen using a fast–freezing procedure on dry ice, with 10% DMSO as the cryoprotectant. AI was performed on 4 different breeds of hens (20 hens per breed) (Rhode Island Red, Potchefstroom Koekoek, New Hampshire and White Leghorn), using fresh semen (control) and frozen-thawed semen. During AI of each breed, 10 hens were inseminated with fresh and the remaining 10 hens with frozen-thawed semen. The sperm characteristics of the semen samples of the 4 breeds recorded were ejaculate volume, ranging from 0.3±0.1 to 0.4±0.1ml, semen pH of 7.6±0.4 to 7.7±0.3, sperm motility (scale of 0-5) 2.8±0.8 to 3.1±0.9, estimated sperm motility 58.8±12.5 to 63.8±13.6%, ejaculate concentration (x109 sperm/ml) of 320.4±286.5 to 748.5±475.3, percentage live sperm 75.6±29.1 to 81.5±26.8%, and the percentage dead sperm 18.6±26.8 to 24.4±29.1% respectively, with the percentage normal sperm ranging between 77.3±17.1 and 84.8±9.0%. Head, mid-piece, tail and other sperm abnormalities of the fresh semen of the 4 breeds ranged from 2.9±3.3 to 7.7±9.6%, 7.9±5.2 to 11.0±7.0%, 0.4±0.8 to 1.9±3.0% and 0.6±0.9 to 1.5±1.9%, respectively. Semen samples were frozen in pellet form on a block of dry ice, by pipetting into the indentations on the surface of the ice. The frozen cockerel pellets were thawed following cryopreservation, by being placed into a test tube in a water bath (60°C), and the tube shaken continuously until complete thawing of the pellet. During the time of semen cryopreservation, a decrease in the number of live, morphologically normal sperm, and increase in the percentage dead sperm and sperm with abnormalities were recorded. The freeze-thawing process caused a significant (P<0.05) decrease in the percentage live sperm and the sperm motility, ranging between 37.4±10.4 and 42.3±12.1% and 3.6±0.5 and 3.9±0.3 respectively. A consequent increase in the percentage of dead sperm (between 57.7±12.1 and 62.4±10.8%) was also recorded. The sperm abnormalities regarding sperm head abnormalities ranged between 17.3±3.8 to 22.5±10.3%, the mid-piece abnormalities 7.9±3.8 to 10.4±2.0% and the tail abnormalities between 0.5±0.9 to 2.0±2.4% respectively for the thawed semen. Frozen-thawed semen was thawed in a water-bath 60°C and hens were inseminated twice per week using the frozen-thawed semen, and once a week with fresh semen for a total period of two weeks. Data for the two trials were analyzed using the ANOVA and the Tukey’s Studentized Range (HSD) test for repeated measures (SAS system General Linear Models Procedure). A total of 973 eggs, from all breeds of chicken namely the Rhode Island Red, Potchefstroom Koekoek, New Hampshire and White Leghorn were collected following AI with fresh and frozen semen from individually caged hens. Eggs were collected, incubated and hatched to check if fertile and normal chicks could be produced from frozen-thawed cockerel semen. The difference in fertility and hatchability of the hens of the different breeds were compared and found to be highest in Rhode Island Red, White Leghorn, and Potchefstroom Koekoek respectively and lowest in New Hampshire using fresh semen. When using frozen-thawed semen, the sequence of fertility performance was the White Leghorn, Rhode Island Red, Potchefstroom Koekoek and New Hampshire, respectively. The effect of the numbers of sperm per AI dose on fertility, age at embryonic death, and hatchability of fertile eggs were also evaluated. Low numbers of sperm per AI in the hens resulted in a decrease in the total number of chicks hatched. The lowest fertility rate recorded was in the New Hampshire (2.7%), when using frozen-thawed semen to inseminate the hens. This may be attributed to the low numbers of sperm inseminated per AI dose. Egg hatchability of the fertile eggs was high in the White Leghorn (13.6%), Rhode Island Red (12.8 %), Potchefstroom Koekoek (9.7 %) and low in New Hampshire (2.7%) respectively, which could possibly be attributed to the egg size. Medium sized eggs were preferable for setting, in order to obtain an acceptable hatch, as they generally hatch better than the larger eggs. The results recorded for fertility and hatchability in the control group (fresh semen), was similar to the results recorded by other researchers, showing that the AI method used was acceptable. There still exists a necessity to develop an ideal cryopreservation method (diluent and freezing procedure), which would allow for acceptable long term storage of cockerel semen in liquid nitrogen (-196°C) for future use and export with minimum loss regarding sperm viability and fertilizing capacity.
Dissertation (M.Sc.Agric. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2009
Keywords: Germplasm resources; Cryopreservation of organs, tissues, etc; Chickens -- Reproduction; Frozen semen